Strengthening critical thinking through debriefing – experiential learning theory: A case study - Zijing Hu (Journal of Education and Health Promotion, 2024)
BACKGROUND: There is a dire need to strengthen students’ critical thinking in clinical training since it is an essential skill in clinical practice to optimize patient care. Debriefing is a formal or informal post-activity discussion that aims to improve learning outcomes, including critical thinking in clinical practice. There is a lack of research that focuses on students’ experiences of debriefing to promote critical thinking in the South African context using experiential learning theory as a theoretical lens. OBJECTIVE: This study aimed to explore South African students’ lived experiences of debriefing to improve critical thinking. MATERIALS AND METHOD: The author employed a qualitative single-case study design within an interpretivist paradigm. A purposive sampling technique was adopted. Six participants were recruited for this study. The author invited the participants to participate in semi-structured interviews. Data were analyzed through the six-step data analysis framework proposed by Creswell. To ensure the trustworthiness, the author employed multiple techniques to improve the credibility, conformability, dependability, and transferability of this study. These techniques included a well-planned research design and methods, thick descriptions of data, and an audit trail that was audited by a second coder. RESULTS: The findings revealed that participants shared positive experiences toward debriefing and furthermore debriefing through optimized student engagement and improved learning outcomes. This study also revealed that students experienced less stress in group debriefings. However, this study also identified some challenges in conducting debriefing. The challenges were primarily related to incompetent facilitators, inappropriate duration of debriefing sessions, and limited space in the clinic. Moreover, small group debriefing is recommended. CONCLUSION: Debriefing is an effective pedagogical approach to optimize critical thinking in clinical practice. It is recommended that debriefing should be implemented as a norm in clinical training at higher education institutions. Further studies are recommended to be conducted at national and international levels.